REGULATING THE BOUNDARY BETWEEN WORK AND SELF: EMERGING LEGAL TENSIONS AROUND SOCIAL MEDIA IN THE WORKPLACE - Buchbach, Jacinta (AoIR Selected Papers of Internet Research, 2014)
Both law and business practice are struggling to grapple with the blurred boundaries of identity in social media. The rapidly increasing importance of social media for both private and work purposes has led to the emergence of new legal challenges arising before, during, and after employment relationships. Existing legal frameworks, based predominantly on offline conceptions of private and public space, are unable to adequately balance the interests of employers in managing their risk and reputation against the legitimate interests of employees in their privacy, speech, and autonomy. The issues are further complicated by the involvement of social media platforms, private entities who play an increasingly important role in governing conduct but are generally not bound by standards of legitimacy or private duties to either employees or employers. This paper maps, evaluates, and explains current legal disputes in common law jurisdictions. I argue that the current legal context is fraught with uncertainty and generally fails to adequately protect the interests of individuals, who face a significant power imbalance against both employers and online intermediaries.